2017
DOI: 10.1080/00016357.2016.1278262
|View full text |Cite
|
Sign up to set email alerts
|

Long term changes in health complaints after removal of amalgam restorations

Abstract: Removal of amalgam restorations was followed by a long term reduction of general health complaints, which was associated with mercury concentration in urine before amalgam removal. Additional studies are needed to confirm the potential mechanisms for the observed reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…34 Additionally, general health complaints have been reported to decrease with the removal of amalgam fillings compared with the decrease in the previous urine mercury level. 26 No difference was found in the mean neurobehavioral evaluation or nerve conduction velocity in children treated with amalgam filling compared with those treated with composite resin. 41 MiRNAs have an important role in basic biological processes, such as apoptosis, proliferation, differentiation, improvement, and inflammation.…”
Section: Discussionmentioning
confidence: 87%
“…34 Additionally, general health complaints have been reported to decrease with the removal of amalgam fillings compared with the decrease in the previous urine mercury level. 26 No difference was found in the mean neurobehavioral evaluation or nerve conduction velocity in children treated with amalgam filling compared with those treated with composite resin. 41 MiRNAs have an important role in basic biological processes, such as apoptosis, proliferation, differentiation, improvement, and inflammation.…”
Section: Discussionmentioning
confidence: 87%
“…However, the improvement of health after amalgam removal is reported to last for many years, [26][27][28] which may reduce the probabil- has been reported to be associated with the reduction of concentration of inorganic mercury in serum 29 as well as the concentration of mercury in urine at baseline before treatment. 27,29 Such associations between symptoms and laboratory parameters cannot be observed by the patients, which makes observation bias an unlikely explanation for the improvements. Regression to the mean and natural recovery can also contribute to symptom reduction; however, the MUPS cohort with similar symptoms at baseline had no improvement.…”
Section: Key Resultsmentioning
confidence: 99%
“…Another possibility is observation bias, since the symptom and quality of life outcomes are documented by self‐report, and patients offered the desired treatment free of charge could possibly exaggerate their improvement. However, symptom reduction after amalgam removal has been reported to be associated with the reduction of concentration of inorganic mercury in serum 29 as well as the concentration of mercury in urine at baseline before treatment 27,29 . Such associations between symptoms and laboratory parameters cannot be observed by the patients, which makes observation bias an unlikely explanation for the improvements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With advancement in technology and materials, there is an increasing tendency to use mercury-free and environmental-friendly materials and avoid the use of dental amalgam [11]. Although there is no strong evidence that amalgam restorations can cause general health symptoms, there are several studies showing that general health complaints are significantly reduced after amalgam removal [12][13][14][15][16]. Using similar data, a recent study showed a considerable reduction of general health complaints after amalgam removal in patients with attribution to their health complaints to amalgam restorations [17].…”
Section: Introductionmentioning
confidence: 99%